2020
DOI: 10.3349/ymj.2020.61.11.909
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated with School Bullying in Students with Autism Spectrum Disorder: A Cross-Cultural Meta-Analysis

Abstract: Through this meta-analysis, we sought to examine the prevalence of, risks for, and factors associated with bullying involvement (victimization, perpetration, perpetration-victimization) among students with autism spectrum disorder (ASD). Additionally, we attempted to examine sources of variance in the prevalence and effect sizes of bullying in students with ASD across studies. Systematic database and literature review identified 34 relevant studies (31 for Western countries, three for Eastern countries). Poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 86 publications
4
32
0
3
Order By: Relevance
“…Traditional bullying can involve physical acts, verbal utterances, social exclusion, property theft, and other behaviors [ 2 ]. Compared with those without ADHD, adolescents with ADHD have higher risks of being victims and perpetrators of cyberbullying [ 3 , 4 , 5 ] and traditional bullying [ 6 , 7 , 8 ]. Victimization in cyberbullying is significantly associated with depression and suicidality in adolescents with ADHD [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional bullying can involve physical acts, verbal utterances, social exclusion, property theft, and other behaviors [ 2 ]. Compared with those without ADHD, adolescents with ADHD have higher risks of being victims and perpetrators of cyberbullying [ 3 , 4 , 5 ] and traditional bullying [ 6 , 7 , 8 ]. Victimization in cyberbullying is significantly associated with depression and suicidality in adolescents with ADHD [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study investigated how the school environment is associated with bullying victimization among seventh graders (aged 12–13 years) with ASD. Bullying victimization, which has been widely examined in other studies [ 22 , 23 ], was analyzed in this study. We examined four types of bullying victimization separately (social exclusion, insults or teasing, extortion, and sexual harassment) and their relationships with the school environment while controlling for individual variables.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement in traditional bullying, such as physical, verbal, and relational bullying, is prevalent among children and adolescents with autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD). A meta-analysis reported that the pooled prevalence estimates for victimization and perpetration of traditional bullying in students with ASD were 67% and 29%, respectively [ 1 ]. A review study also found that children with ASD are bullied by peers at a rate three to four times that of nondisabled peers with negative impacts on academic functioning and mental health symptoms, including increased risk for suicidality [ 2 ].…”
Section: Introductionmentioning
confidence: 99%